Monopolist, Aristocrat, or Entrepreneur?: A Comparative Perspective on the Future of Multidisciplinary Partnerships in the United States, France, Germany, and the United Kingdom After the Disintegration of Andersen Legal - Mary C. Daly (Washington University Law Quarterly, 2002)
Part II provides a snapshot of the history of multidisciplinary partnerships in France, Germany, and the United Kingdom and the responses of the organized bars at the national and international level. Part III explores how the structure, culture, and ethics of the legal professions in Western Europe contributed to the rapid growth of MDPs. Part IV examines the economic threat that the Big Five’s legal networks posed to U.K. and Western European law firms prior to the criminal conviction of Andersen and the consequent disintegration of Andersen Legal, its law firm network. Part V offers some preliminary reflections on how Andersen’s demise will shape the future of MDPs in the United States, the United Kingdom, and Western Europe. The Conclusion connects that future to deeply embedded competing models of the legal profession.
Keywords: Multidisciplinary practices; Legal ethics; Comparative law; Arthur Andersen LLP; Law firms; Multidisciplinary law firms; Partnerships; Practice of law; France; Germany; United Kingdom; United States